Upregulation of polycistronic microRNA-143 and microRNA-145 in colonocytes suppresses colitis and inflammation-associated colon cancer. Issue 12 (2nd December 2021) - Dougherty, Urszula; Mustafi, Reba; Zhu, Hongyan; Zhu, Xiaorong; Deb, Dilip; Meredith, Stephen C.; Ayaloglu-Butun, Fatma; Fletcher, Michelle; Sanchez, Arantxa; Pekow, Joel; Deng, Zifeng; Amini, Nader; et al.
ABSTRACT: Because ADAM17 promotes colonic tumorigenesis, we investigated potential miRNAs regulating ADAM17; and examined effects of diet and tumorigenesis on these miRNAs. We also examined pre-miRNA processing and tumour suppressor roles of several of these miRNAs in experimental colon cancer. Using TargetScan, miR-145, miR-148a, and miR-152 were predicted to regulate ADAM17. miR-143 was also investigated as miR-143 and miR-145 are co-transcribed and associated with decreased tumour growth. HCT116 colon cancer cells (CCC) were co-transfected with predicted ADAM17-regulating miRNAs and luciferase reporters controlled by ADAM17-3'UTR. Separately, pre-miR-143 processing by colonic cells was measured. miRNAs were quantified by RT-PCR. Tumours were induced with AOM/DSS in WT and transgenic mice (Tg) expressing pre-miR-143/miR-145 under villin promoter. HCT116 transfection with miR-145, −148a or −152, but not scrambled miRNA inhibited ADAM17 expression and luciferase activity. The latter was suppressed by mutations in ADAM17-3'UTR. Lysates from colonocytes, but not CCC, processed pre-miR-143 and mixing experiments suggested CCC lacked a competency factor. Colonic miR-143, miR-145, miR-148a, and miR-152 were downregulated in tumours and more moderately by feeding mice a Western diet. Tg mice were resistant to DSS colitis and had significantly lower cancer incidence and tumour multiplicity. Tg expression blocked up-regulation of putative targets of miR-143 and miR-145, including ADAM17, K-Ras, XPO5, and SET. miR-145, miR-148a, and miR-152 directly suppress colonocyte ADAM17 and are down-regulated in colon cancer. This is the first direct demonstration of tumour suppressor roles for miR-143 and miR-145 in an in vivo model of colonic tumorigenesis.